Feasibility of Creation of an Endovascular Arteriovenous Fistula in Patients Undergoing Preoperative Vascular Mapping. Issue 2 (24th February 2022) - Al-Balas, Alian; Varma, Rakesh; Sharbidre, Kedar; Al-Balas, Hassan; Almehmi, Ammar; Abdel Aal, Ahmed Kamel; Robbin, Michelle L.; Allon, Michael
Key Points: Among patients who were eligible for a surgical fistula, 63% were suitable for endoAVF. Older patients were less likely to have a vascular anatomy suitable for an endoAVF. Patients with a vascular anatomy suitable for an endoAVF were similar in sex, race, DM, HTN, CAD, and peripheral artery disease. Visual Abstract: Abstract : Background: The first endovascular arteriovenous fistula (endoAVF) device (WavelinQ), a novel percutaneous technique of AVF creation, was approved by the Food and Drug Administration in 2018 and has been placed in a small number of United States patients on hemodialysis. It is unknown how often patients with advanced CKD have vascular anatomy suitable for WavelinQ creation. The goal of this study was to determine the proportion of patients with vascular anatomy suitable for WavelinQ creation and to assess patient characteristics associated with such suitability. Methods: All patients referred for vascular access placement at a large academic medical center underwent standardized preoperative sonographic vascular mapping to assess suitability for an AVF. During a 2-year period (March 2019 to March 2021), we assessed the suitability of the vessels for creation of WavelinQ. We then compared the demographic characteristics, comorbidities, and vascular mapping measurements between patients who were or were not suitable for WavelinQ. Results: During the study period, 437 patients underwent vessel mapping. Of these, 51% of patients were eligible for a surgical AVF, and 32% were eligible for a WavelinQ AVF; 63% of those suitable for a surgical AVF were also suitable for a WavelinQ AVF. Patients with a vascular anatomy suitable for WavelinQ were younger (age 55±15 versus 60±14 years, P =0.01) but similar in sex, race, diabetes, hypertension, coronary artery disease, and peripheral artery disease. Conclusions: Among patients with CKD with vascular anatomy suitable for a surgical AVF, 63% are also suitable for a WavelinQ endoAVF. Older patients are less frequently suitable for WavelinQ.